Superior charge storage performance of optimized nickel cobalt carbonate hydroxide hydrate nanostructures for supercapacitor application - Mohit Bhatt; Bhavana Gupta; A. K. Sinha (Scientific Reports)
Abstract In our work, we report superior electrochemical performance of optimized 3D nanostructured, nickel-cobalt carbonate hydroxide hydrate (Ni3 − xCox-CHH (1 ≤ x ≤ 2)) materials with flower like morphology synthesised via one-step hydrothermal methods. A Ni rich sample (x = 1) demonstrate better specific capacitance and the improvement is attributed to more oxygen deficient neighbourhood of Ni compared to that of Co. The structural, morphological and electronic properties of the samples were investigated using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), High resolution transmission electron microscopy (HRTEM), field emission electron microscopy (FESEM), Energy-dispersive X-ray spectroscopy (EDX), and X-ray photoelectron spectroscopy (XPS). A comprehensive characterization was used for physicochemical properties-electrochemical performance correlation. Cyclic voltammetry (CV), Galvanostatic charging and discharging (GCD) shows the supercapacitor feature of the samples for the composition containing the highest nickel concentration achieving a specific capacitance of 1649.51 F g− 1 at a current density of 1 A g− 1 and excellent rate capability of 1610.30 F g− 1 at a high current density of 5 A g− 1. The sample shows high cyclic stability of 80.86% after 3000 cycles. Improved specific capacitance is attributed to the synergy effect of bimetallic transition metals as well as improved surface area of flower like morphology. These findings show that Ni2Co-CHH electrode material demonstrates great potential as electrode material for supercapacitor device fabrication.